THE IMPORTANCE OF DISTINGUISHING LEADERSHIP FROM MANAGEMENT IN TODAY’S WORLD - Julianto, Pebi; Agrisa Ditama, Rezki; Amin Hadi, Al (Qawwam : The Leader's Writing, 2025)
This study seeks to reexamine the significance of the distinction between leadership and management within the ever-evolving and unpredictable environment of modern organizations. Employing a qualitative methodology through an extensive literature review, the research delves into the nuanced roles and interconnectedness of leadership and management in contemporary organizational settings. While traditional literature often treats leadership and management as separate domains, this study highlights a shifting paradigm toward their unification within a single professional role. The study’s key contribution lies in its emphasis on a holistic and strategic approach to human resource development, aimed at cultivating individuals who can fulfill both managerial and leadership functions. Findings suggest that maintaining a strict conceptual divide between leadership and management is increasingly outdated, particularly within high-performing organizations. Consequently, there is a growing need for organizational policies that integrate both skill sets into employee training, career progression, and performance appraisal systems. Ultimately, the research concludes that the success of modern organizations depends on the synergy, not the separation of leadership and management.